Implementation of Community-Based Waste Management to Improve Environmental Health in Villages - Utami; Titis Istiqomah; Lieza Corsita (Sustainable Applied Modification Evidence Community (SAMEC), 2024)
Waste management has emerged as a critical environmental issue, particularly in rural areas where population growth and changing consumption patterns have led to increased waste generation. This research focuses on the implementation of community-based waste management in villages, aiming to understand its impact on environmental health and the factors influencing program success. Utilizing a quantitative analytic approach with a cross-sectional research design, the study surveyed 4,345 family heads, with a sample size of 98 participants.The findings revealed that 54.1% of respondents did not engage in waste management activities. Among these non-participants, 70.4% had low educational attainment (elementary or junior high school). Additionally, 53.1% cited a lack of infrastructure as a barrier to participation, while 64.3% reported poor knowledge of waste management practices.The results indicated that infrastructure availability significantly influences community participation, with a p-value of 0.006 and an odds ratio (OR) of 3.911. Furthermore, knowledge levels were crucial; those with inadequate knowledge were less likely to participate (69.2% did not engage), whereas those with good knowledge showed higher participation rates (63%).Effective waste management is essential for improving environmental health by reducing pollution and disease risks. Therefore, enhancing education and infrastructure is vital to encourage community involvement in waste management initiatives. This study underscores the importance of addressing knowledge gaps and infrastructural challenges to foster sustainable waste management practices in rural communities.